A comparison of water curing and standard curing on one-part alkali-activated fly ash sinking beads and slag: Properties, microstructure and mechanisms. (1st March 2021) - Wei, Tangzhong; Zhao, Hu; Ma, Cong
Highlights: Water curing causes the higher crystallinity degree of products and coarser microstructure in one-part geopolymer. Composite activator including sodium carbonate can improve the water resistance of one-part geopolymer. The difference in early-term hydration products and pore distribution of one-part geopolymer explain the mechanisms. Abstract: The commonly used curing regime in one-part AAFSS is air curing or sealed standard curing. In this research, one-part alkali-activated fly ash sinking beads and slag (AAFSS) was prepared by using composite activators. The difference between standard curing and water curing was investigated, and the influencing mechanism of water curing was also studied. Experimental results indicate that the strength after 28 days of water curing stops increasing, and even decreases to some extent. The use of ultra-fine fly ash sinking beads (FASB) and Na2 CO3 can ameliorate the water resistance index defined as the ratio of compressive strength of specimens after the same days of standard curing and water curing. And the acid resistance of water-curing AAFSS is poorer than that of standard-curing AAFSS. The mechanical properties and durability of one-part AAFSS after water curing are affected by ions leaching and destruction of microstructure. XRD and TG-DTG analysis reveal that 28 days of water curing does not change the types of hydration products, but decreases the number of gelatinous products and calcite. An interesting finding is that the intensity of diffraction peaks of gelatinous products of specimens under water curing is higher than that under standard curing. Water curing makes the microstructure much coarser, and large microfracture could be found in SEM images. The use of FASB and Na2 CO3 can improve the microstructure of one-part AAFSS after water curing.